2020
DOI: 10.1111/are.14639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary mulberry leaf extract on the growth, gastrointestinal, hepatic functions of Chinese giant salamander ( Andrias davidianus )

Abstract: Mulberry leaf extract (MLE), an active substance extracted from mulberry leaves, is known to have a positive effect on several physiological functions. The current study examined the effects of dietary MLE in feed at concentrations 0, 3.0, 6.0, 9.0, 12.0 and 15.0 g/kg on the growth performance and gastrointestinal and hepatic functions of Andrias davidianus for 12 weeks. Results indicated that the final body weight, weight gain rate (WGR), specific growth rate and feed intake (FI) of A. davidianus increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Therefore, high starch diet supplemented with MLE decreased lipid and glycogen deposition by enhancing glucose and lipid metabolism. In addition, the whole-body moisture and muscle were significantly decreased in the MLE groups, which was consistent with results previously obtained in the Chinese giant salamander (Andrias davidianus) (Li Z et al, 2020). Antioxidant enzyme systems are an important defense mechanism of organisms, which can reduce peroxide in the body into less harmful substances (Bogdan et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, high starch diet supplemented with MLE decreased lipid and glycogen deposition by enhancing glucose and lipid metabolism. In addition, the whole-body moisture and muscle were significantly decreased in the MLE groups, which was consistent with results previously obtained in the Chinese giant salamander (Andrias davidianus) (Li Z et al, 2020). Antioxidant enzyme systems are an important defense mechanism of organisms, which can reduce peroxide in the body into less harmful substances (Bogdan et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…To date, only a few studies on mulberry leaf extract (MLE) in aquaculture have been reported. Dietary MLE can improve the growth performance, feed utilization, digestive capacity, and hepatic antioxidant status of the Chinese giant salamander (Li Z et al, 2020). Mulberry leaf extract can also alleviate Aeromonas hydrophila infection of African catfish (Clarias gariepinus) (Sheikhlar et al, 2014;Sheikhlar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ash is an indication of mineral content of food and it has been reported that watermelon seed has high ash content (Ojinnaka et al 2018;Falade et al 2020). Crude fibre is known to aid the digestive system of human (Jin et al 2020;Li et al 2020). Energy is a function of the protein, fat and carbohydrate composition of any food product which could be the reason for variation in the energy values of the products (Ojinnaka et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The same observation was found in other study by Fujaya et al (2014) where a high frequency of moulting in larvae of blue swimming crab, Portunus pelagicus was observed when fed with mulberry leaves extract. A previous study by Li et al (2020) showed that the final body weight, weight gain rate, specific growth rate and feed intake of Chinese giant salamander, Andrians davidianus were increased with the increase in the dietary of mulberry leaves extract up to 9.0 g/kg and declined subsequently, while the feed conversion ration exhibited an opposite trend.…”
Section: Body Weight and Body Length Of Post Larvae M Rosenbergiimentioning
confidence: 93%